Estimation of Genetic Parameters of Cayenne Peppers (Capsicum Annuum L.) from IPB University for Its Resistance Against Begomoviruses in Aceh - Hafsah, Siti; Ardika, Aiyu; Hayati, Erita; Firdaus, Firdaus (Yayasan Pertanian Tropika Indonesia (YPTI), 2020)
The productivity of pepper plants is strongly influenced by climatic and weather conditions as well as pests and diseases. One of the major losses in chili farming is the pest attack, such as whiteflies (Bemisia tabaci Genn.), a virus vector. Evaluation of the resistance of pepper plant germplasm against Begomovirus infection needs to be carried out, evaluate genetic diversity, estimate heritability values, and obtain a selection character for the resistance of chili plants Begomovirus. This research was conducted at Experimental Garden, Faculty of Agriculture, Universitas Syiah Kuala, and the Laboratory of Genetics and Plant Breeding, Faculty of Agriculture, Universitas Syiah Kuala from January to May 2020. Three varieties Gada, Anies and Selekta with seven test genotypes i.e F6 Gada, Seloka 4-10-2-2, F5136074-1-4-3, F5074136-2-3-2, F5074035-2-1-2, F5074035-2-4-2, F5074077-1-1-3 were screened for their resistance against Begomovirus. This study was designed using a non-factorial Randomized Block Design (RBD) and scoring parameter Begomovirus symptom. Tukey’s HSD, the standard deviation of genetic variance, heritability, and correlation were performed to analyze the data. The lowest disease intensity occurred in genotype F6 Gada with a percentage of 12.08% disease intensity (slightly resistant), and the highest level of disease intensity occurred in F5074035-2-4-2 with a percentage of 30.94% (susceptible). Variables symptom scoring, disease intensity, and incubation period were the most effective variables for selecting pepper resistance against Begomovirus infection based on broad-sense heritability values.